2012
DOI: 10.1007/s10600-012-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in α-tocopherol, some minerals, and fatty acid contents of wheat through sprouting

Abstract: In this study, two wheat cultivars (cvs Demir 2000 and Konya 2002) were sprouted at 17qC and 85% relative humidity for 9 days. Then the wheat sprouts were dried and ground. The wheats and their sprouts were analyzed for D-tocopherol, some minerals, and fatty acid contents during the sprouting. The D-tocopherol contents of cvs Demir 2000 and Konya 2002 were 26.99 and 23.77 mg/kg, respectively, and these values reached 54.62 and 47.19 mg/kg for their sprouts, respectively. Mineral analyses showed that the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…These results for fatty acid composition were within ranges reported in some wheat cultivars [35,36] and cereals like Sorghum bicolor [35,36] and Eleusine coracana. [37] The content of linoleic acid in the tested oils range from 29.52 to 39.58% and was followed by palmitic acid which was also present in high amounts varying from 24.10% up to 35.83%.…”
Section: Resultssupporting
confidence: 84%
“…These results for fatty acid composition were within ranges reported in some wheat cultivars [35,36] and cereals like Sorghum bicolor [35,36] and Eleusine coracana. [37] The content of linoleic acid in the tested oils range from 29.52 to 39.58% and was followed by palmitic acid which was also present in high amounts varying from 24.10% up to 35.83%.…”
Section: Resultssupporting
confidence: 84%
“…Sprouting increases the bioavailability of protein and starch. Wheat sprouts are characterised by a low content of unsaturated fatty acids and higher contents of vitamins and minerals such as phosphorus, calcium, zinc and copper (Ozturk et al ., ; Žilić et al ., ). The content of polyphenolic compounds in wheat sprouts is usually higher than in dormant seeds; however, the increase is usually insignificant (Alvarez‐Jubete et al ., ; Hung et al ., ; Benincasa et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The method described by Ozturk et al . () was used for the wheat sprout production. At first, wheat grains were soaked in tap water at 17 °C for 24 h. In this period, the grains absorbed the water, and germination enzymes were activated.…”
Section: Methodsmentioning
confidence: 99%
“…This may be attributed to the strong bioactive compounds present in the wheat sprouts (Falcioni et al, 2002;Calzuola et al, 2004Calzuola et al, , 2006. It has been well demonstrated that wheat sprouts contain a powerful cocktail of antioxidant molecules such as a-tocopherol, polyphenols and reducing glycosides (Ozturk et al, 2012;Marsili et al, 2004). In addition to the positive effect of these compounds present WSPs on retardation of lipid peroxidation, contribution of black pepper and red pepper, which are known as powerful radical scavengers, should be also taken into consideration (Gulcin, 2005;Sim & Sil, 2008).…”
Section: Lipid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation